Under the banner of heaven (Colorado State Library Book Club Collection): a story of violent faith (Anchor Books, 2004)
Traces the events that surrounded the 1984 murder of a woman and her child by fundamentalist Mormons Ron and Dan Lafferty, exploring the belief systems and traditions that mark the faith's most extreme factions.

The fate of gender (Colorado State Library Book Club Collection): nature, nurture, and the human future (Bloomsbury, 2016)
"Frank Browning takes us into human gender geographies around the world, from gender-neutral kindergartens in Chicago and Oslo to femminielli weather casters in Naples, from conservative Catholics in Paris fearful of God and Nature to transsexual Mormon parents in Utah. As he shares specific and engaging human stories, he also elucidates the neuroscience that distinguishes male and female biology, shows us how all parents' brains change during the first weeks of parenthood, and finally how men's and women's responses to age differ worldwide based not on biology but on their earlier life habits. Starting with Simone de Beauvoir's world-famous observation that one is not born a woman but instead becomes a woman, Browning goes on to show equally that no one is born a man but learns how to perform as a man, and that there is no fixed way of being masculine or feminine. Increasingly, the categories of "male" and "female" and even "gay" and "straight" seem old-fashioned and reductive. Just visible on the horizon is a world of gender and sexual fluidity that will remake our world in fundamental ways. Linking science to culture and behavior, and delving into the lives of individuals challenging historic notions, Browning questions the traditional division of Nature vs. Nurture in everything from plant science to sexual expression, arguing in the end that life consists of an endless waltz between these two ancient notions"--
Gender visions. Simple justice or gender chaos? ; From homemakers to nation builders , Nature, nurture, and society. Science and society ; Who is woman? ; Show us what you're made of ; Gender war , Family values : new realities, new complexities. Start at the very beginning ... ; Bringing up baby ; Parents and storks ; Rebuild the hearth and humanize the firm? , Fluidities. Transitions ; That can't be sex ; Is the clitoris a sex organ? ; Sexual capital in Shanghai , Gender and being. Gender and the techno mind ; Bodies and brains ; Gender and resilience.